Simulation and optimization of a butane autothermal reformer for fuel cell - Abdullah, Mohammad Sharir; Hasbullah, Hasrinah; Ibrahim, Norzana; Abd. Hamid, Kamaruddin (Faculty of Chemical and Natural Resources Engineering, 2007)
Hydrogen (H2) production is gaining popularity among researchers for a better future environment. Hydrogen, which is known as the cleanest fuel, is also an excellent candidate to replace existing fuels. Its high flammability and energy produced with no side product make it even more popular. In this study, a steady-state model simulation is developed to describe a butane fuel processor by autothermal reforming (ATR) to provide H2 for fuel-cell application. The objective of the study is to develop a general steady-state simulation of an H2 production plant for fuel cell application using butane as the feedstock. The scope of the study includes stoichiometric mathematical analysis, base case steady-state simulation, base case simulation validation, the design of heat integration, carbon monoxide (CO) clean-up processes which contains water gas shift (WGS) and preferential oxidation (PrOx) reactors and plant wide optimization. The simulation has been run in Aspen HYSYS 2004.1 in steadystate mode in which optimization was done to generate more H2 as well as CO reduction. The butane fuel processor was optimized at Oxygen-to-Carbon (O/C) ratio of 2.18 and Steam-to-Carbon (S/C) ratio of 4.6 to produce 39.2 % of H2 and has achieved 78.1 % efficiency, while CO clean-up units was capable to reduce the CO concentration down to 10 ppm